1977
DOI: 10.1111/j.1095-8649.1977.tb04042.x
|View full text |Cite
|
Sign up to set email alerts
|

The primary immune response of brown trout (Salmo trutta) to injection with cellular antigens

Abstract: The primary immune response of brown trout (Salmo trutta L.) was studied after injections of two cellular antigens-Salmonella typhi H, flagellar antigen d, and human group ' 0 ' Rh+ red blood cells. Both intraperitoneal and intramuscular injections were employed. Agglutinins and complement-fixing antibodies were produced to S. typhi and haemagglutinins to human ' 0 ' red blood cells. Maximum titres to S. typhi were reached after 49 days in the case of both agglutinins and complement-fixing antibody. Haemagglut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Whilst previous studies on salmonids have found mean serum protein concentrations between 3.9 and 8.0 g 100 ml -I (Booke, 19640, b ;Ingram, 1974;Ingram &Alexander, 1977;Meisner & Hickman, 1963;Mulcahy, 1975;Snieszko, Miller & Atherton, 1966), no attempt at such a computation was made in the present work. This was because (i) there was a significant difference between the means for male and female fish, and (ii) within each sex there was a significant difference between the means obtained for each year.…”
Section: Discussionmentioning
confidence: 88%
“…Whilst previous studies on salmonids have found mean serum protein concentrations between 3.9 and 8.0 g 100 ml -I (Booke, 19640, b ;Ingram, 1974;Ingram &Alexander, 1977;Meisner & Hickman, 1963;Mulcahy, 1975;Snieszko, Miller & Atherton, 1966), no attempt at such a computation was made in the present work. This was because (i) there was a significant difference between the means for male and female fish, and (ii) within each sex there was a significant difference between the means obtained for each year.…”
Section: Discussionmentioning
confidence: 88%
“…Brown trout (1 +, 115-315 mm) were obtained from the Dunsop Bridge Trout Farm, Dunsop Bridge, near Clitheroe, Lancashire and maintained in an air-conditioned room at 11-13" C. The methods of maintenance and transport were as previously reported (Ingram & Alexander, 1977).…”
Section: Maintenance Of Fishmentioning
confidence: 99%
“…The presence of antibody acitivity in sera and serum fractions was investigated by complement fixation, indirect haemagglutination (IHA) and counter-current electrophoresis (CCE) as described previously (Ingram, 1978;Ingram & Alexander, 1976, 1977.…”
Section: Detection Of Antibody Activitymentioning
confidence: 99%
“…Precipitins. Sera were examined for the presence of precipitating antibodies by gel diffusion, countercurrent electrophoresis, and immunoelectrophoresis as previously reported (17,19). In the cases of gel diffusion and countercurrent electrophoresis, the sera were challenged against a sonicated antigen extract ranging in concentration from 0.1-30 mg/ml, and with immunoelectrophoresis the amount was 50 mg/ml.…”
mentioning
confidence: 99%
“…The complement fixation test was used to estimate the titers of complement-fixing antibodies in toad sera as previously described (18). The sonicated antigen extract was used at a concentration of 10 mg/ml protein, rabbit hemolysin was diluted 1 : 400 with complement fixation test buffer and ShE were used at a 2% suspension.…”
mentioning
confidence: 99%